1998
DOI: 10.1111/j.1750-3639.1998.tb00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic and Knockout Mice in Research on Prion Diseases

Abstract: Since the discovery of the prion protein (PrP) gene more than a decade ago, transgenetic investigations on the PrP gene have shaped the field of prion biology in an unprecedented way. Many questions regarding the role of PrP in susceptibility of an organism exposed to prions have been elucidated. For example mice with a targeted disruption of the PrP gene have allowed the demonstration that an organism that lacks PrPc is resistant to infection by prions. Reconstitution of these mice with mutant PrP genes allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 144 publications
0
19
0
3
Order By: Relevance
“…Furthermore, PrP Sc like proteins produced in vitro have not yet been shown to be infectious 6. The strongest evidence for the prion hypothesis comes from experiments with transgenic mice7showing that mice lacking the PrP gene are not able to propagate infectivity and develop the disease. Use of these mice in neural graft experiments has proved that PrP c is necessary for the spread of the TSE infectious agent along neuronal pathways 8.…”
Section: Prion Hypothesismentioning
confidence: 99%
“…Furthermore, PrP Sc like proteins produced in vitro have not yet been shown to be infectious 6. The strongest evidence for the prion hypothesis comes from experiments with transgenic mice7showing that mice lacking the PrP gene are not able to propagate infectivity and develop the disease. Use of these mice in neural graft experiments has proved that PrP c is necessary for the spread of the TSE infectious agent along neuronal pathways 8.…”
Section: Prion Hypothesismentioning
confidence: 99%
“…It is majorly expressed in neuronal cells where TSE-associated damages occur. Knockout experiments (1) have not unraveled any physiological role of PrP C . However, ex vivo studies using cells from PrP null mice or prion-infected cells revealed alterations in copper metabolism and enhanced susceptibility to oxidative stress (2,3).…”
mentioning
confidence: 99%
“…There is compelling genetic evidence that transmission of TSEs is tightly controlled by the PrP-encoding gene (Prnp) (38,40,52). Apart from modulating the individual susceptibility to the disease through natural polymorphism or mutation, PrP appears to play a critical role in determining the prion host range.…”
mentioning
confidence: 99%